Molecular landscape of prostate cancer: Implications for current clinical trials. Issue 9 (November 2015) - Khemlina, Galina; Ikeda, Sadakatsu; Kurzrock, Razelle
Highlights: Improvement of prognosis with androgen-deprivation therapy in prostate cancer has plateaued. Next-generation sequencing reveals the recurrent genomic aberrations in prostate cancer. Potential matched-targeted therapies are available in actionable genetic alterations, such as PTEN and PIK3CA. Biomarker-matched therapy (other than for androgens) have been utilised in only 2.0% of clinical trials. Enhanced efforts for molecular targeted therapy warrant more investigation. Abstract: Castration-resistant prostate cancer (CRPC) is a lethal disease, and improvement with androgen-deprivation therapy has plateaued. Next-generation sequencing studies have led to significant advances in our understanding of genomic alterations in prostate cancer. The most common genomic aberrations in this malignancy are the transcription factor fusion of TMPRSS2 – ETS, and mutations in TP53, AR, RB1 and PTEN / PIK3CA . Some of these alterations are actionable by drugs available in the clinic. In addition, it was recently shown that aberrations in DNA repair genes, such as BRCA2 and ATM, are present in both somatic and germline form in a significant minority of prostate cancer; these abnormalities can be targeted by drugs such as platinums and PARP inhibitors. In the era of tumour profiling, targeting molecular alterations may provide an opportunity for new therapeutic approaches. Although there are promising new agents to attack a variety of genomic signal abnormalities, biomarker-matched therapy (other than for androgens) have been utilised in only 2.0% of clinical trials (September 2011 through September 2014; https://clinicaltrials.gov ) for prostate cancer. Enhanced efforts to define subsets of patients with prostate cancer based on their molecular anomalies, and match them with cognate therapies, warrant investigation.